A comprehensive review of electric discharge machining of advanced ceramics. Issue 14 (1st October 2020) - Ming, Wuyi; Jia, Haojie; Zhang, Hongmei; Zhang, Zhen; Liu, Kun; Du, Jinguang; Shen, Fan; Zhang, Guojun
Abstract: Advanced ceramics are widely used in high temperature and wear related situations due to their unique physical and chemical characteristics. With the increasing demand for ceramics, the machining techniques of ceramics become a hot and tough issue because ceramics are extremely fragile and difficult to process. Traditional mechanical machining techniques like milling, turning, and drilling are subjected to large cutting forces and heat leading to extensive tool wear and poor machining performance. Electric discharge machining (EDM) has an outstanding ability of no-contact machining brittle and hardness materials with complex shapes via generating extreme high-temperature plasma channel to melt and vaporize materials. Therefore, in this paper, the research trends of latest EDM technologies for advanced ceramic materials were comprehensively reviewed. Firstly, according to the electrical conductivity of advanced ceramics, different EDM processes were introduced in details. Secondly, the existing physical models and material removal mechanisms of EDM process of ceramics were compared and analyzed. Then the machining performance indicators, such as MRR, Ra, TWR, surface topography, and micro-structures, were respectively investigated. Additionally, the new hybrid machining techniques of EDM were presented to provide some potential for efficiently machining advanced ceramics. Eventually, this paper also discussed the challenges associated with electrical discharge machining of advanced ceramic materials, and suggested some related research areas which possibly attract significant research attentions in the future. Highlights: A comprehensive review is proposed from the perspective of machining performance for ED machining advanced ceramics. The present physical models and material removal mechanisms of ED machining advanced ceramics are discussed. The latest hybrid machining techniques of EDM used in the process of advanced ceramics are presented.